2016
DOI: 10.14740/jocmr2440w
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and Character Profiles and Psychiatric Comorbidities in Patients With Coronary Artery or Valvular Heart Disease: Relationship With Cardiac Disease Severity

Abstract: BackgroundWe aimed to investigate whether the psychopathological symptoms and temperament-character dimensions observed in patients operated due to coronary artery disease (CAD) or valvular heart disease (VHD) differ among the patients and from healthy individuals.MethodsStudy population was composed of subjects with CAD, VHD and healthy controls (n = 50 in each group). Socio-demographic questionnaire, temperament and character inventory (TCI) and symptom check list-90-R (SCL-90-R) were applied to all groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It was revised by Dağ (11) considering our country. There are many studies conducted in Turkey on its use in non-pregnancy related pathologies (38)(39)(40). Two studies were published on its use for the assessment of patients diagnosed with hyperemesis gravidarum in the first trimester of pregnancy from our country (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…It was revised by Dağ (11) considering our country. There are many studies conducted in Turkey on its use in non-pregnancy related pathologies (38)(39)(40). Two studies were published on its use for the assessment of patients diagnosed with hyperemesis gravidarum in the first trimester of pregnancy from our country (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several authors have reported significant associations between type D personality (negative affectivity and social inhibition) [464,465] and depressive or irritable temperament [466,467]. The causes of these associations are not fully understood, but in the case of type D personality, adverse lifestyle choices predictive of CVD development appear to be an important factor while irritable temperament is predictive of increased vascular stiffness and hypertension [465,468,469].…”
Section: Socioeconomic Behavioural and Psychosocial Factors In The Dementioning
confidence: 99%
“…41,42 MDD is a major risk factor of CAD. 43 MDD is also a major risk factor of persistent angina. 44 Depression is a major risk factor of angina, and depressive patients can show a poor prognosis even after revascularization surgery if the depression is not treated.…”
Section: Depression Coronary Artery Disease and Obstructive Sleep Apneamentioning
confidence: 99%